Poverty and Human Development Index: An Inter-District Study in Central Sulawesi - Farah Aziza; Mohamad Ichwan (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
Central Sulawesi Province consists of 13 districts/cities with varying levels of poverty. The numbers fluctuate in the period of time of 2013 to 2020 were classified as high because they were ranked 2nd (second) compared to other provinces on the island of Sulawesi. The low quality of human capital is one of the main causes of poverty, to see the achievement of human capital investment, the education dimension is represented by the average length of schooling, the expected length of schooling, and the health dimension is represented by life expectancy, which is a measure in efforts to build the quality of human life showing an increase consistently. Increasing the quality of human capital is expected to improve the productivity of the poor. Therefore, the purpose of this research was to determine the effect of Average Length of Schooling, Expected Length of Schooling, and Life Expectancy on poverty levels in Central Sulawesi Province. This was a quantitative research. Data used was secondary data out of 13 districts/cities in Central Sulawesi Province for the period of 2013–2020. The data was analyzed using panel data analysis with a random effect regression model. The results show that the Average Length of Schooling variable has a positive effect and is proven to increase poverty, Expected Length of Schooling has a negative effect and is proven to reduce poverty, Life Expectancy has a negative effect and is not proven to reduce poverty, Life Expectancy2 has a positive effect and is not proven to increase poverty in Central Sulawesi Province for the 2013-2020 period.